A Study on the strengthening of internet control system for securing financial soundness of state-owned enterprises - AHN, Duck Hoon (KDI School, 2023)
tate-owned enterprises (SOEs) in Korea are heavily indebted. As of the end of 2020, public sector debt (D3), including debt from non-financial SOEs, amounted to 1,280 trillion won, accounting for 66.2% of GDP (FIS, 2022). Although the size of government debt is still stable, the situation changes when considering the debt of SOEs. This is because governments have used SOEs as a top priority tool for achieving the policy goals of the regime as an alternative to limited government finances. A representative SOE is K-water. K-water is a public institution whose financial soundness has greatly deteriorated by participating in the government's key policy projects, and is also the institution whose financial structure is improving the fastest through its own efforts since then. In other words, we can analyze the main causes of SOEs’ debt and find alternatives through a case study on K-water. K-water invested about KRW 11 trillion by participating in the Four Major Rivers Project and the Gyeong-in Ara Waterway construction project, and the debt ratio of 19.6% in 2008 soared to 211.4% in 2015. In the process of participating in these projects, there was no internal financial decision-making standard, and the internal control system did not work at all. As a result, K-water has become a financially poor institution and is still required to make high-intensity self-rescue efforts. Since then, in order not to repeat the case of the Four Rivers Project, the highest internal regulation, the financial management rules, has been established. The core content is the accounting pay-go principle that limits the increase in debt to within the increase in capital. Since the introduction of the rules, K-water's financial structure has been radically improved every year. However, this achievement was possible thanks to the absolute will of the management including the CEO to improve the financial structure by complying with the financial rule and the consent of the government that approved the financial plan established in accordance with K-water's internal rule. In other words, the financial rule established by the institution itself is just internal regulation and has no external binding force. In addition, the limitations are clear because the government can control all decisions of SOEs through the ‘Act on the Management of Public Institutions’, regardless of the internal regulations of SOEs. Comparing the OECD Guidelines (2015 Edition), which requires a clear distinction between guaranteeing the autonomy of SOEs and the exercise of government ownership, the Act has a strong control purpose, such as the government's active ownership exercise and supervision. Therefore, it is desirable for the government to control SOEs by setting the financial limit of SOEs within a certain range, and for SOEs to carry out autonomous and responsible management activities within that boundary. This paper suggests the following three measures for maintaining the financial soundness of SOEs. First, in order to strengthen the legal authority and basis of SOEs’ internal control measures, it is required to prepare a legal basis for the internal control system of SOEs. This is a plan to introduce a case of compliance management standards of listed companies based on ‘the Commercial Act’ to the ‘Act on the Management of Public Institutions’ to obligate the introduction and implementation of financial management rules for each institution. In other words, it enacts and manages financial rules for each company through laws. Second, regulations such as the financial management rule introduced by K-water should be established to secure internal decision-making standards for SOEs themselves. It is to establish the rules for each institution by specifying the relevant standards that each institution implicitly uses for financial management, such as mid- to long-term financial plans. Third, the professionalism, responsibility, and authority of the board of directors of SOEs, which are the main body that operates the financial management standards, should be strengthened.
Thesis(Master) -- KDI School: Master of Public Management, 2023
Keywords: Government business enterprises--Finance--Korea (South); Water-supply--Korea (South)